ANALGESIC ЕFFECT OF 25% GLUCOSE AND NON-NUTRITIVE SUCKING IN TERM NEWBORNS - COMPATIVE ANALYSIS - Penka Petleshkova; Maya Krasteva; IIliyana Pacheva; Nataliya Vilmosh; Snezhana Dragusheva (Peytchinski Publishing, 2022)
Non-nutritive sucking and oral uptake of glucose 25% are often non-pharmacological methods used to manage procedural pain in newborns. Aim: To compare the effect of using non-nutritive suction (NNS) and Sol.Glucosae 25% for reducing/eliminating neonatal pain due to heel prick. Material and methods: Term infants were studied: group (A), NNS, n = 40, and group (B) oral uptake of Sol.Glucosae 25%, n = 40. The severity of procedural pain was assessed using the Neonatal Facial Coding System (NFCS) scale: 30 seconds before the procedure, at the 30th second and at the 5th minute after the procedure. Physiological pain markers were monitored at these intervals: respiratory, heart rate, transcutaneous saturation (tSpO2), arterial blood pressure. Results and Discussion: Newborns in a group (B) had a lower evaluation at the 5th minute compared to those treated with non-nutritive suckling(A). There are significant differences in heart rate, breathing frequency and before the procedure. The intake of Sol. Glucose 25% compared to NNS causes a higher heart rate and a decrease in at the 30th second after the painful procedure. In contrast to the heart rate, for respiratory rate and tSpO2 at 5th min. we reported lower than the norms in both groups A and B. Conclusion: Unlike NNS, glucose intake eliminates pain within 5 minutes after a heel prick. Excluding arterial blood pressure, all other physiological pain markers undergo changes before the procedure but not after it.